2022
DOI: 10.1002/er.8366
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of electron mobility and thermoelectric power factor of cobalt‐doped n ‐type Bi 2 Te 3

Abstract: We report the enhancement of electron mobility and power factor for 3D topological insulator Bi 2 Te 3 with Cobalt (Co) doping. Thermal variation of resistivity (ρ), thermopower (S), carrier concentration (n H ), magneto-resistance (MR), and magnetization measurements have been performed on synthesized Cobalt-doped n-type Bi 2 Te 3 , viz., Bi 2Àx Co x Te 3 (x = 0, 0.05, and 0.1) samples. Theoretical simulation of electrical and thermal transport parameters has been done in the frame of the Boltzmann equation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 59 publications
4
7
0
Order By: Relevance
“…Ni inclusion significantly increases the PF to ∼2415 µWm −1 K −2 , which is more than three times higher than that of the pristine counterpart. Such high PF value was reported for Co-doped Bi 2 Te 3 samples with Co-doping [14]. However, for Sb 2 Te 3 -based system such high PF has rarely been reported, to the best of our knowledge.…”
Section: Electronic Propertiessupporting
confidence: 47%
See 1 more Smart Citation
“…Ni inclusion significantly increases the PF to ∼2415 µWm −1 K −2 , which is more than three times higher than that of the pristine counterpart. Such high PF value was reported for Co-doped Bi 2 Te 3 samples with Co-doping [14]. However, for Sb 2 Te 3 -based system such high PF has rarely been reported, to the best of our knowledge.…”
Section: Electronic Propertiessupporting
confidence: 47%
“…Interestingly, it has been observed that most of the binary chalcogenide-based 3D TIs, e.g., Bi 2 Te 3 , and Sb 2 Te 3 attract significant attention for their exceptional thermoelectric (TE) performance [13,14]. However, unlike its TM-doped counterpart, not much work has been reported to study the TE performance of TM-doped tetradymites.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, no shift of the Bi 2 Te 3 ‐related XRD peaks was discerned, proving that the PPy coating did not affect the Bi 2 Te 3 crystal structure. Similarly, Raman spectroscopy showed Bi 2 Te 3 @PPy inherits the characteristic signals of both Bi 2 Te 3 and PPy (Figure 2i and Figure S7b, Supporting Information), displaying the E u 1 , E g 2 , and A 1g 2 vibrational modes of Bi 2 Te 3, [ 29 ] and the D and G bands of carbonaceous materials. [ 30,31 ] Likewise, Fourier‐transform infrared spectroscopy results also showed the Bi 2 Te 3 @PPy to contain the fingerprints of both materials, Bi 2 Te 3 and PPy (Figure S8, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…A higher zT of 1.07 at 423 K was observed in CuI-doped Bi 2 Te 2.7 Se 0.3 processed by hotdeformation [22]. Similarly, Co doping was used to enhance the electrical transport properties of pristine Bi 2 Te 3 and ptype Bi 0.5 Sb 1.5 Te 3 [23,24].…”
Section: 대한금속 • 재료학회지 제61권 제3호 (2023년 3월)mentioning
confidence: 98%